PENGARUH RASIO KEUANGAN DAN PERUBAHAN PAJAK DIVIDEN TERHADAP DIVIDEND PAYOUT RATIO PERUSAHAAN TERBUKA - Cahyo Dwi Sulistiyo; Sri Hartoyo; Tb Nur Ahmad Maulana (Jurnal Keuangan dan Perbankan, 2016)
AbstractThe objective of this research was to analyse influence company performance ratio such as ROA, DER, Size,EPS, Current Ratio, Growth and changes in dividend tax rates to Dividend Payout Ratio. The variables testedusing panel regression analysis. Research conducted on 40 emitens included in LQ 45 index of Indonesia StockExchange (ISE) with years of research covering 2006 to 2012. The panel regression results show that thevariables ROA, Current Ratio, Size, andGrowth showed a significant effect on dividend payout ratio,while thevariable DER, EPS, and Tax have no significant effect on the dividend payout ratio but all the variablesimultaneously influential to dividend payout ratio.